Integration of multicultural values in Civic Education learning through research-based learning - Ella Kusuma Wardani; Unik Ambar Wati; Fery Muhammad Firdaus; Lisa Retnasari; David Lailelleru (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2026)
The complex dynamics of Indonesia's pluralistic society necessitate innovative approaches to reconstruct Civic Education paradigms, specifically through the integration of multicultural values. This study investigates the implementation of Research-Based Learning (RBL)—operationalised through a systematic cycle of observation, data collection, analysis, conclusion, and application—as an innovative pedagogical model at Sanggar Anak Alam (SALAM). Employing a qualitative case study design, the research engaged 35 participants, comprising facilitators, students, and parents. Data were systematically gathered via in-depth interviews, participant observations, and document analysis, followed by thematic analysis and triangulation facilitated by ATLAS.ti software. The analysis yielded two primary findings: firstly, the embedding of multicultural values significantly enhances appreciation for diversity and cultivates an inclusive character amongst students; secondly, RBL effectively fosters civic competencies by actively engaging students in resolving contextualised social issues. These findings demonstrate that this model not only fortifies the internalisation of multicultural values but concurrently refines students' critical cognitive abilities, empathy, and collaborative skills. Ultimately, this framework exhibits substantial potential for adaptation within formal educational settings, thereby enriching the Civic Education curriculum to become more culturally responsive. This innovation posits a novel paradigm wherein inclusive pedagogy ensures equitable educational access, the RBL cycle refines instructional methodologies, and insights derived from non-formal education serve as a viable catalyst for fortifying institutional Civic Education.